Stem Cells in Equine Veterinary Practice—Current Trends, Risks, and Perspectives - Katarzyna Kornicka (Journal of Clinical Medicine, 2019)
With this Editorial, we introduce the Special Issue “Adipose-Derived Stem Cells and Their Extracellular Microvesicles (ExMVs) for Tissue Engineering and Regenerative Medicine Applications„ to the scientific community. In this issue, we focus on regenerative medicine, stem cells, and their clinical application.